2020
DOI: 10.1136/archdischild-2020-320616
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in children treated with immunosuppressive medication for kidney diseases

Abstract: BackgroundChildren are recognised as at lower risk of severe COVID-19 compared with adults, but the impact of immunosuppression is yet to be determined. This study aims to describe the clinical course of COVID-19 in children with kidney disease taking immunosuppressive medication and to assess disease severity.MethodsCross-sectional study hosted by the European Rare Kidney Disease Reference Network and supported by the European, Asian and International paediatric nephrology societies. Anonymised data were subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 24 publications
(24 reference statements)
3
52
0
Order By: Relevance
“…Overall mortality was 16% and this might be a reflection of high incidence of non-COVID sepsis and associated complications in these patients. In a study on 113 children with kidney diseases receiving immunosuppressive medications from 30 countries; authors found that only 9.7% had severe grade of disease [3]. Features of relapse, or new organ involvement (pancreas) or new onset glomerulonephritis have been seen in children with nephrotic syndrome in present study and this might be like other viruses, SARS Co-V-2 infection may also precipitate relapses or infect new organ [9,10].…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Overall mortality was 16% and this might be a reflection of high incidence of non-COVID sepsis and associated complications in these patients. In a study on 113 children with kidney diseases receiving immunosuppressive medications from 30 countries; authors found that only 9.7% had severe grade of disease [3]. Features of relapse, or new organ involvement (pancreas) or new onset glomerulonephritis have been seen in children with nephrotic syndrome in present study and this might be like other viruses, SARS Co-V-2 infection may also precipitate relapses or infect new organ [9,10].…”
supporting
confidence: 51%
“…There is limited information about susceptibility to SARS-CoV-2 infection, clinical profile and outcome among immunocompromised children in India. Published literature has revealed milder disease and favorable outcome without discontinuation of immunosuppressive medication in these children [2][3][4][5][6]. We, herein describe the clinical features and outcome of immunocompromised children diagnosed with SARS-CoV-2 infection at our center.This was a retrospective analysis of data from 1 June to 31 October, 2020 at a tertiary care center of a teaching hospital.…”
mentioning
confidence: 91%
“…From the SARS-CoV2 worldwide spread, only few evidence of SARS-CoV2 infection in children with chronic kidney disease were reported. A global study reported no case of severe illness or MIS-C in 113 children with kidney disease in immunosuppressive therapy [5]. Also, a Spanish retrospective study of 26 patients [8] and two case reports [9] described a mild clinical course of infection in children with kidney disease, with no case of PICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations in children are generally milder than in adults, with a lower hospitalisation rate and need for intensive care support [2]. Moreover, while chronic kidney disease (CKD) and hypertension (HT) have been described as important risk factors for severe SARS-CoV2 in adults [3], in the paediatric population, these comorbidities are apparently unrelated with a severe course of the disease [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Limited data exist on SARS-CoV2 implications in children with other kidney diseases requiring chronic immunosuppression, such as nephrotic syndrome or glomerulonephritis. One retrospective study across 30 countries from the early waves of March to July 2020 included only 113 children with SARS-CoV2 positivity and chronic immunosuppression for kidney diseases, approximately half of whom were transplant patients [ 53 ]. The study was limited by the self-reporting nature of participating nephrologists but demonstrated that those impacted with SARS-CoV2 had similar reassuring rates of hospitalization, need for respiratory support, and mortality as children not treated with chronic immunosuppression [ 53 ].…”
Section: Sars-cov2 Infection In Special Pediatric Nephrology Populationsmentioning
confidence: 99%